2007
DOI: 10.1021/jf071776n
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific Rice Hybrid of Oryza sativa × Oryza nivara Reveals a Significant Increase in Seed Protein Content

Abstract: Wild species offer a potential reservoir of genetic variation for crop improvement. Besides the valuable genes for disease resistance that the wild species have provided for rice improvement, recent studies have shown that these wild species could also provide favorable alleles for the improvement of yield and yield-related traits. The present study reports yet another potential of wild relatives of rice, which involves the improvement of seed protein content. A significant increase in seed protein content was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 27 publications
1
25
0
Order By: Relevance
“…[21,22] reported that deposition of protein in rice grains depends on plethora of interrelated metabolic pathways involved in uptake of N, Fe and Zn from soil, their transport to source tissues such as culms and leaves and mobilization and/or remobilization to developing grains. Each of these processes is governed by several genes and influenced by environmental factors such as soil type, drought, fertilizers application, genotype, environment interaction [23,24].…”
Section: Proximate Compositionmentioning
confidence: 99%
“…[21,22] reported that deposition of protein in rice grains depends on plethora of interrelated metabolic pathways involved in uptake of N, Fe and Zn from soil, their transport to source tissues such as culms and leaves and mobilization and/or remobilization to developing grains. Each of these processes is governed by several genes and influenced by environmental factors such as soil type, drought, fertilizers application, genotype, environment interaction [23,24].…”
Section: Proximate Compositionmentioning
confidence: 99%
“…, 1997), the study of these species have an interesting potential to unveil genetic traits associated with different stress resistance. Indeed, some reports have been recently published on this topic (Mahmoud et al. , 2008; Fukao et al.…”
Section: Introductionmentioning
confidence: 99%
“…Although major reproductive barriers exist between plants belonging to different genome groups, and the rate of success for intergenomic crosses is very low (Yan et al, 1997), the study of these species have an interesting potential to unveil genetic traits associated with different stress resistance. Indeed, some reports have been recently published on this topic (Mahmoud et al, 2008;Fukao et al, 2009;Koseki et al, 2010;Li et al, 2010;Philippe et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Without significant increases to the protein content of rice grain, it appears certain that the severity of PEM as a global nutritional disorder will increase significantly under future, CO 2 -enriched atmospheres. Grain protein content does, however, show considerable variability across rice varieties and conventional breeding may be a viable strategy for producing new cultivars with increased grain protein content (Kennedy and Burlingame 2003;Mahmoud et al 2008).…”
Section: Rice As a Staple Food In 2050 And Beyond -Assessing The Impamentioning
confidence: 99%